Land-use change impacts on soil processes tropical and savannah ecosystems - Brearley, Francis Q.; Thomas, Andrew D. (Andrew David), 1970- (CABI, 2015)
This book contains a collection of 14 case studies from around the globe that illustrate the impact of a range of land-use changes on the physical, chemical and biological characteristics of soils and provide a snapshot of the challenges faced in ensuring sustainable soil management in tropical and savannah environments. This book is not a comprehensive account of all the drivers of soil change in the tropics, nor does it cover all areas of the tropics. It does, however, take a broad view of the tropics, with the inclusion of studies from South Africa and the dry sub-humid tropics of the Kalahari as well as the humid tropics. Tropics are drawn from a wide geographical area including South and Central America, South East Asia, India and Africa, and the chapters have been contributed by authors from all of these areas as well as Europe, North America, Australasia and Japan. It thus provides a snapshot of a range of factors affecting soils across the globe. From this, emerges topics that can be grouped into the following themes: the effects of land-use change on soil microbial populations; urban soils, agriculture and soil contamination; and land-use effects on soil carbon and soil organic matter.